Identification of STN7/STN8 kinase targets reveals connections between electron transport, metabolism and gene expression. (21st April 2017) - Schönberg, Anna; Rödiger, Anja; Mehwald, Wiebke; Galonska, Johann; Christ, Gideon; Helm, Stefan; Thieme, Domenika; Majovsky, Petra; Hoehenwarter, Wolfgang; Baginsky, Sacha
Summary: The thylakoid‐associated kinases STN7 and STN8 are involved in short‐ and long‐term acclimation of photosynthetic electron transport to changing light conditions. Here we report the identification of STN7/STN8 in vivo targets that connect photosynthetic electron transport with metabolism and gene expression. Comparative phosphoproteomics with the stn7 and stn8 single and double mutants identified two proteases, one RNA‐binding protein, a ribosomal protein, the large subunit of Rubisco and a ferredoxin‐NADP reductase as targets for the thylakoid‐associated kinases. Phosphorylation of three of the above proteins can be partially complemented by STN8 in the stn7 single mutant, albeit at lower efficiency, while phosphorylation of the remaining three proteins strictly depends on STN7. The properties of the STN7‐dependent phosphorylation site are similar to those of phosphorylated light‐harvesting complex proteins entailing glycine or another small hydrophobic amino acid in the −1 position. Our analysis uncovers the STN7/STN8 kinases as mediators between photosynthetic electron transport, its immediate downstream sinks and long‐term adaptation processes affecting metabolite accumulation and gene expression. Significance Statement: The thylakoid‐associated kinases STN7 and STN8 are involved in long‐term acclimation processes that entail changes in gene expression; however, information on the mediators and the signal processing is currently missing. We identified previously unknown STN7/STN8 phosphorylation targets that show a connection between photosynthetic electron transport and the phosphorylation of proteins involved in metabolism and gene expression, thus unraveling previously unknown links that can now be studied in detail.